Sur les traces de Virgolino, un cangaceiro dit Lampião - Patricia Sampaio Silva (Cahiers des Amériques Latines)
The famous Brazilian bandits known as cancageiros were considered in turn as infrarevolutionaries, social bandits, honorable bandits and, more recently, as the mere armed hands of local potentates. Numerous works deal with the life of Lampião, the leader of the most famous gang. The phenomenon of banditism, designated by the term cangaço, remains, nevertheless, largely misunderstood. This misunderstanding originates in the semi-arid zones where these gangs ruled mercilessly and were viewed as stereotypes. It is in the goal of providing an alternative explanation of the fate of Virgololino, who later became the bandit Lampião, that his footsteps have been traced while still a young man, across the Pajeú Valley, in the back country of the state of Pernambuco and in particular Villa Bella and Floresta. His story provides a means of returning to «village» life and of interweaving his trajectory with that of all the others who, with him, made up this population and who never knew a similar fame.